Активность звезды Gl 414A с двумя планетами и ее влияние на потерю массы атмосферой планеты Gl 414A b - Саванов, И. С. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Представлены результаты исследования проявлений активности карлика спектрального класса K7 Gl 414A с двумя планетами, одна из которых (планета Gl 414A b) при эксцентриситете е = 0.45 на протяжении большей части своей орбиты находится в пределах зоны обитаемости. Наш анализ показал, что наиболее достоверным определением периода вращения Gl 414A следует признать результаты анализа фотометрических наблюдений звезды, выполненных обзором Kilodegree Extremely Little Telescope (KELT), указывающие на период ее вращения Р = 42 сут. We present the results of the analysis of the manifestations of the activity of K7 dwarf Gl 414A with two planets, one of which (planet Gl 414A b) with an eccentricity of e = 0.45 is located within the habitable zone for the most part of its orbit. Our analysis showed that the most reliable result of determining the rotation period of Gl 414A should be obtained while the analysis of photometric observations of the star performed by the KELT survey, indicating the rotation period of the star P = 42 days, which, however, is absent on periodograms constructed from other observations.
Keywords: Астрофизика